The Influence of Playing with Number Blocks on the Increase in Counting Ability in Class 4 Mental Retardation Children in SDLB/C Aditama Surabaya - Zuhrina Irma A’tiana; Reliani Reliani; Mundakir Mundakir; Era Catur Prasetya (Universitas Muhammadiyah Semarang, 2016)
Background: The number block is a media that Montessori created in 1909. This block media is made of a wooden square and consists of 10 blocks with red and blue colors. Each red and blue segment represents the sum of 1 block. According to Fridani in Kompas Daily (2010), the block game itself has several advantages, including that children can recognize mathematical concepts because by playing blocks, children get to know more concepts - less, the same and not the same, the concepts of numbers and numbers and science. Such as calculating, classification, gravity, and stabilization.Objective: To determine the effect of number blocks on increasing numeracy skills in mentally disabled childrenMethod: The research design was a pre-experimental design with one group pre-test - a post-test design approachResults: Before being given the intervention to play numeric blocks, most of the ten respondents (59%) had the level of numeracy (analyzing number symbols, addition, and subtraction) in children with mental retardation, which was in the low category. Mental is in the good category for eight respondents (47%), and five respondents (29%) are included in the good category.Conclusion: There is an effect of numeracy skills on children with mental retardation before and after the intervention to play number blocks.